The Correlation between Student Interest in English Songs and Listening Skills of 5th Semester Students of the University of Pasir Pengaraian - Eripuddin; Pipit Rahayu; Azi Nurazima Juhastri; Dimas Haikal Fahlafi; Miftahul Jannah Alpahmi; Sukma Rani Putri; Nduru, Iman Ria (Journal of Classroom Action Research, 2025)
This study investigates the correlation between students' interest in listening to English songs and their listening skills among 5th-semester students at the University of Pasir Pengaraian. Employing a quantitative correlational research design, data were collected from 25 students through questionnaires assessing their interest in English songs and a listening test measuring their comprehension skills. The findings revealed a weak positive correlation (r = 0.131) between students' interest in listening to English songs and their listening skills. This suggests that while students who enjoy listening to English songs may demonstrate slightly better listening abilities, the relationship is not statistically significant. The results indicate that listening skills are influenced by multiple factors beyond interest in songs. While integrating music into learning may create an engaging atmosphere, it should not be solely relied upon for improving listening skills. The study suggests incorporating structured listening exercises and interactive methods alongside music to enhance students’ comprehension.